A Review of the Impact of Bush Burning on the Environment: Potential Effects on Soil Chemical Attributes - Alhaji Maigana Chiroma; Abdullahi Bala Alhassan (International Journal of Science and Environment (IJSE), 2023)
Bush burning, whether the result of a wildfire or a controlled burn, has been shown to affect not only the appearance of the landscape, but the quality of the soil as well. Uncontrolled bush fires impact the soil in a variety of ways with the magnitude of the disturbance largely dependent upon the fire intensity, duration and recurrence, fuel load, and soil characteristics. The impact on soil properties is intricate, yielding different results based on these factors. Whereas burning off the vegetation during land clearing for cultivation is a common farming practice among farmers in many parts of the tropics, yet little is known by perpetrators of this practice about its impacts on the soil and its dwellers. This paper reviews research findings from a number of works conducted across the globe with the aim of gaining an insight the effects of wildfire and prescribed fire on the soil chemical and biological attributes. The knowledge of soils response in terms of these two properties to fire events can help in proper implementation of rehabilitation and restoration strategies at the short term, medium term, and long term.